A Review on The AC Servo Motor Control Systems (ELEKTRIKA- Journal of Electrical Engineering, 2020)
AC Servomotors are widely used in the industries for the control of static and dynamic loads. Precise control of position, speed, and torque are the main issues with the AC Servomotor. AC Servomotors are highly demanded by the industries to have a precise response under dynamic load conditions. Many control techniques are commercially available for the control of AC Servomotor under static and dynamic load conditions. However, all of these control techniques have advantages and limitations. Many investigations are done on the control of AC Servomotor, but comprehensive surveys on the control of AC Servomotor were still limited. In this paper, most of such commercially available control techniques are investigated, discussed, and compared.
Keywords: AC Servomotor; Control Stability; Dynamic Load; Static Load; Step Response; Control System